Inosine supplementation effectively provokes the growth, immune response, oxidative stress resistance and intestinal morphology of juvenile red sea bream, Pagrus major. (22nd July 2016) - Hossain, M.S.; Koshio, S.; Ishikawa, M.; Yokoyama, S.; Sony, N.M.; Usami, M.; Ono, S.; Fujieda, T.
Abstract: A feeding trial was conducted to determine effects of dietary inosine on growth, immune responses, oxidative stress resistance and intestinal morphology of juvenile red sea bream. A semi‐purified basal diet supplemented with 0 (D1, control), 2 g kg −1 (D2), 4 g kg −1 (D3), 6 g kg −1 (D4) and 8 g kg −1 (D5) dietary inosine, respectively, to formulate five experimental diets. Each diet was randomly allocated to triplicate groups of fish (initial weight: 8 g). After 50 days of feeding trial, fish fed diets with 4 g kg −1 inosine had the highest ( p < .05) final weight, weight gain and specific growth rate. Similarly, improved feed intake, feed conversion ratio and protein efficiency ratio were also found at 4 g kg −1 inosine supplemented group. Some non‐specific immune parameters such as total serum protein, lysozyme activity and bactericidal activity tended to be higher for fish fed diets supplemented with inosine. Peroxidase and catalase activity also influenced ( p < .05) by dietary inosine supplementation. Fish fed 2 g kg −1 and 4 g kg −1 inosine supplemented diets showed the least oxidative stress condition. Inosine supplementation significantly increased ( p < .05) anterior enterocyte height and posterior fold height, enterocyte height and microvillus height compared with control. We concluded that 4 g kg −1 dietary inosine supplementation effectively provokes growth and health performance of red sea bream by increasing growth, immune response, oxidative stress resistance and intestinal health condition.